2018
DOI: 10.1039/c8tc03011a
|View full text |Cite
|
Sign up to set email alerts
|

Use of the time constant related parameter fmax to calculate the activation energy of bulk conduction in ferroelectrics

Abstract: The use of time constant related parameter fmax to obtain the activation energy for bulk electrical conduction (and any discussion of the possible conduction mechanisms) in ferroelectric materials should be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…With Sn 4+ doping concentration increases, the radius of arc decreases and maybe because the increase of Sn 4+ reduces the height of grain boundary barrier at this temperature, thus leading to the change of impedance [30]. Besides, a small tail appears on the periphery of the arc in low-frequency range of some graphs (such as x = 0, 0.1, 0.2 and 0.25), which may be related to the electrode effect [31]. Following discussion will ignore it, due to the limit of measurement frequency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With Sn 4+ doping concentration increases, the radius of arc decreases and maybe because the increase of Sn 4+ reduces the height of grain boundary barrier at this temperature, thus leading to the change of impedance [30]. Besides, a small tail appears on the periphery of the arc in low-frequency range of some graphs (such as x = 0, 0.1, 0.2 and 0.25), which may be related to the electrode effect [31]. Following discussion will ignore it, due to the limit of measurement frequency.…”
Section: Resultsmentioning
confidence: 99%
“…According to the equivalent circuit fitting results and combined Z and M plots, the dielectric response mainly comes from three aspects: grain core, grain shell and grain boundary. Combined with the R and C values, the lowfrequency responses are related to grain boundary (R 3 , C 3 , n 3 ), and the high frequency responses are involved with the grain core (R 1 , C 1 , n 1 ) and grain shell (R 2 , C 2 , n 2 ) [31,33]. The insets in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This has been conrmed by our previous studies on the electrical properties of NBT-BiAlO 3 (NBT-BA), NBT-BiGaO 3 (NBT-GB) and NBT-BiScO 3 (NBT-BS) solid solutions. 23,24 s b of NB 0.50 T can be signicantly reduced aer incorporation of these Bi-based perovskites. The ability of B-site acceptordopants to trap oxygen vacancies depends on their ionic size.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Defect mechanisms. For xed-valence M (M 3+ as an example), previous studies have demonstrated that dominant defect mechanisms in NBT-BiMO 3 can be described by: 23,24 Na…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation